Role of Technology in the Development of Smart Cities - Miah, Md. Shelim; Amin, Ruhul (Engineering International, 2020)
The key aim of this paper is to address the technical effects of smart city growth. While the smart city issue has been discussed in recent literature, it is of interest if macro ICT considerations should also be considered for determining a city’s technical advancement. First of all, literature analysis of a smart city is presented to accomplish this purpose. Along with a theoretical structure focused on the information community, an overview of the smart city idea is included. The ICT development of Smart Cities depends on the characteristics and features of the cities, as well as on macro-technological considerations. Cities that use information technology as a means of urban sustainability build smartness to emerge as smart cities as a source of constant growth and transformation within the urban ecosystem, pursuing a managerial and organizational vision of sustainability. The aim of this thesis is to suggest a theoretical overview of the city as a sustainable society that drives urban development and adopts a smart urban growth vision.